2016
DOI: 10.1038/srep37796
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional characterization of the major lymphocyte populations in the fruit-eating bat Pteropus alecto

Abstract: The unique ability of bats to act as reservoir for viruses that are highly pathogenic to humans suggests unique properties and functional characteristics of their immune system. However, the lack of bat specific reagents, in particular antibodies, has limited our knowledge of bat’s immunity. Using cross-reactive antibodies, we report the phenotypic and functional characterization of T cell subsets, B and NK cells in the fruit-eating bat Pteropus alecto. Our findings indicate the predominance of CD8+ T cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 52 publications
4
41
1
Order By: Relevance
“…Very few bat-specific antibodies that identify immune cell populations exist. To overcome this obstacle, Martinez Gomez et al and Periasamy et al screened commercially available antibodies for cross-reactivity to cells isolated from blood and primary and secondary lymphoid tissues of P. alecto bats (120,121). Using monoclonal antibodies specific to mammalian transcription factors, Martinez Gomez et al found that wildcaught P. alecto bats displayed a predominance of CD8+ T cells in the spleen, whereas CD4+ T cells were the most prevalent lymphocyte in the blood, lymph nodes, and bone marrow.…”
Section: Immune Cell Populations In Batsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few bat-specific antibodies that identify immune cell populations exist. To overcome this obstacle, Martinez Gomez et al and Periasamy et al screened commercially available antibodies for cross-reactivity to cells isolated from blood and primary and secondary lymphoid tissues of P. alecto bats (120,121). Using monoclonal antibodies specific to mammalian transcription factors, Martinez Gomez et al found that wildcaught P. alecto bats displayed a predominance of CD8+ T cells in the spleen, whereas CD4+ T cells were the most prevalent lymphocyte in the blood, lymph nodes, and bone marrow.…”
Section: Immune Cell Populations In Batsmentioning
confidence: 99%
“…Most studies on bat immune-relevant cells have been carried out on cells from fruit bats. Functional characterization of bat T and B cells have been carried out by detecting cytokines that are secreted by these cells on stimulation (120,121). NK cells from P. alecto and E. spalaea have been detected by flow-cytometry (121).…”
Section: Modulation Of Antiviral Responsesmentioning
confidence: 99%
“…Given the general absence of clinical signs of disease in bats infected with the same viruses that are so lethal in humans or other non-natural hosts infected experimentally, a critical question has been to understand whether bats might establish effective disease tolerance, thus maintaining fitness despite pathogen replication, or whether bats are more resistant to infection through more successful control of pathogen replication and what the contribution of the immune response is (65,66). The lack of many fundamental immunological tools enabling the probing of bat immune responses has meant that truly mechanistic studies of bat immunity have been very limited, although recently there has been some progress in establishing approaches such as flow cytometry to identify distinct bat immune cell populations (67,68). So far, studies of bat immunity have primarily taken one of three approaches, whereby each comes with important strengths and weaknesses that have to be kept in mind: (i) comparative genome studies, (ii) in vitro cell culture assays, and (iii) experimental infections.…”
Section: Anti-viral Immune Responses Of Batsmentioning
confidence: 99%
“…This allows bats to more specifically and effectively target pathogens, but likely at the expense of immune processes that generate high antibody levels (titers) . In addition, in wild‐caught P. alecto , immune cells called T cells that are classically involved in antiviral responses in other mammals seem to co‐occur with other T cell subsets that regulate immune response . This suggests that cell‐mediated immunity in bats may be biased toward regulatory and anti‐inflammatory processes.…”
Section: Changing Resource Landscapes and Henipavirus Spillovermentioning
confidence: 99%